Prediction of Pathologic Response in Unresectable Hepatocellular Carcinoma After Downstaging with Locoregional and Systemic Combination Therapy - Yang C; Chen Y; Sheng L; Wang Y; Zhang X; Yang Y; Ronot M; Jiang H; Song B (Journal of Hepatocellular Carcinoma)
Chongtu Yang,1,2,* Yidi Chen,1,2,* Liuji Sheng,1,2 Yanshu Wang,1,2 Xiaoyun Zhang,3 Yang Yang,4 Maxime Ronot,5 Hanyu Jiang,1,2 Bin Song1,2,6 1Department of Radiology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2Functional and Molecular Imaging Key Laboratory of Sichuan Province, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Division of Liver Surgery, Department of General Surgery, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 4Cancer Center, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 5Department of Radiology, Hôpital Beaujon (Université de Paris), Clichy, France; 6Department of Radiology, Sanya People’s Hospital, Sanya, Hainan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hanyu Jiang; Bin Song, West China Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China, Email hanyu_jiang@foxmail.com; songlab_radiology@163.comBackground: The combination of locoregional and systemic therapy may achieve remarkable tumor response for unresectable hepatocellular carcinoma (HCC).Objective: We aimed to investigate the correlation between radiologic and pathologic responses following combination therapy, evaluate their prognostic values, and to establish a non-invasive prediction system for pathologic response.Methods: This single-center retrospective study included 112 consecutive patients with HCC who underwent locoregional and systemic combination therapy followed by liver resection or transplantation. Radiologic response was assessed with Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 and modified RECIST (mRECIST). Pathologic necrosis percentage was assessed to determine major pathologic response (MPR, ≥ 90% tumor necrosis) and pathologic complete response (100% tumor necrosis). Performance of the response criteria in predicting pathologic response was assessed with the area under the receiver operator characteristic curve (AUC).Results: Among all radiologic and pathologic response criteria, MPR was the only independent predictor of post-resection recurrence-free survival (RFS) (adjusted hazard ratio 0.34, 95% CI 0.16– 0.72, p=0.004). In addition, mRECIST showed stronger correlation with pathologic response than RECIST 1.1 (spearman r values: 0.76 vs 0.42, p< 0.001). A prediction system for MPR was developed that included a combination of mRECIST response (ie, > 70% decrease of viable target lesions) with either > 90% decrease in AFP (for AFP-positive group, n=75) or > 80% decrease in PIVKA-II (for AFP-negative group, n=37), which yielded a respective AUC of 0.905 and 0.887. Furthermore, the system-defined dual-positive responders showed improved median RFS (not reached) than non-responders (7.1 months for AFP-positive group [p=0.043] and 13.3 months for AFP-negative group [p=0.099]).Conclusion: mRECIST was more indicative of pathologic response after combination therapy than RECIST 1.1. Integration of mRECIST with AFP or PIVKA-II responses allowed for accurate prediction of MPR and could support decision-making on subsequent curative-intent treatment.Keywords: hepatocellular carcinoma, chemoembolization therapeutic, systemic therapy, pathologic response, response evaluation criteria in solid tumors